Los medios informáticos: tratamiento procesal (2008)
The automation in the last times has served him great to the administration of justice having made agile its procedures and making possible an expeditious access but to the laws, the doctrine and the jurisprudence. The administration of Justice cannot give the back to the tecnologic reality and to the advantages that of her are given off. It is a reality that the daily life social this impregnated of the use of new technologies of the communication. The management of the courts leans every time but in the computer science. In this writing argue in the use and the efficiency and assessment of the proofs held in means informatics. In the present work one looks for to differentiate means in electronic support and what they can contain like test source, in addition it is indicated as they are the requirements of promotion, contribution and valuation that must fulfill so that as average probatory is used in judgment and is guaranteed the due process. It is a study of documentary character of conceptual and morphologic type, using the compared right.